2014
DOI: 10.1021/np5001363
|View full text |Cite
|
Sign up to set email alerts
|

Amethystin, the Coloring Principle of Stentor amethystinus

Abstract: Among the ciliates, Stentor amethystinus stands out for its conspicuous red-violet color compared to its blue- and red-colored relatives Stentor coeruleus and Blepharisma japonicum. Rich blooms in German lakes allowed us to collect sufficient organisms to isolate the pigments and elucidate the structure of the main component amethystin (4) by spectroscopic methods as a carboxy derivative of blepharismin. Depending on conditions, the carboxy group appears as an orthoester or as a mixture of the orthoester and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Summarizing, the Blepharisma species studied are able to defend themselves against C. hirtus, although S. sphagnetorum and S. roeseli seem to overcome Blepharisma's chemical defense, but it was observed that after the ingestion of intact cells of the toxic ciliates these predators are not able to reproduce, suggesting the presence of the post-ingestion toxicity phenomena [56]. Additional toxic pigments, structurally related to hypericin, were found in other heterotrich ciliate species, such as stentorin in S. coeruleus (see [57] for a review), amethystin in S. amethystinus [58], and maristentorin in the marine ciliate Maristentor dinoferus [59], but the defensive function was experimentally proved only for S. coeruleus [60].…”
Section: The Chemical Defensementioning
confidence: 99%
“…Summarizing, the Blepharisma species studied are able to defend themselves against C. hirtus, although S. sphagnetorum and S. roeseli seem to overcome Blepharisma's chemical defense, but it was observed that after the ingestion of intact cells of the toxic ciliates these predators are not able to reproduce, suggesting the presence of the post-ingestion toxicity phenomena [56]. Additional toxic pigments, structurally related to hypericin, were found in other heterotrich ciliate species, such as stentorin in S. coeruleus (see [57] for a review), amethystin in S. amethystinus [58], and maristentorin in the marine ciliate Maristentor dinoferus [59], but the defensive function was experimentally proved only for S. coeruleus [60].…”
Section: The Chemical Defensementioning
confidence: 99%
“…In other studies, the secondary metabolites produced by a ciliate were simply analyzed after rough cell extractions, generally using organic solvents. However, through this procedure, information about the original cell localization of the analyzed substances was lost and not always deducible .…”
Section: Quantitative Effect On the Number Of Extrusome‐deprived Cellmentioning
confidence: 99%
“…Blepharismins and stentorins are both characterized by a hypericin‐like skeleton. Similar compounds have been recently isolated, including maristentorin from the marine ciliate Maristentor dinoferus 15 and amethystin from the freshwater ciliate Stentor amethystinus 16…”
Section: Introductionmentioning
confidence: 67%